Sliding Mode Control of Induction Machine - Singh, Sumit (My University, 2008)
Sliding mode control is versatile and has simple design procedure; this methodology has proven to be one of the most powerful solutions for many practical control designs. This thesis is analysis application aspects of sliding mode control methodology. First the design approach based on the regularization is generalized for a electrical system. The application in this thesis is related to control of induction machine. The task in this thesis is to control the induction machine dynamics using Sliding Mode Control. The induction motor constitutes a system which in addition to perturbations and uncertainties due to modelling imprecision, hold the difficulty of being highly time variant. In order to be able to keep required performance with uncertainties and modelling imprecision present, the use of robust control methods like Sliding Mode Control is necessary. SMC is based on the states of the system being forced to stay on or in the direct vicinity of a hyper plane in the state space which is chosen in a way that gives the system dynamics desired properties. Other advantages with sliding mode are reduced order dynamics on the switching surface and total insensitivity to some uncertainties and perturbations.
Keywords: mode induction machine